Risk factors for lower-extremity injuries in female ballet dancers: A systematic review - Biernacki, J. I.; Stracciolini, A.; Fraser, J.; Micheli, L. J.; Sugimoto, D. (Clinical Journal of Sport Medicine, 2021)
Background: Ballet dancers have a high prevalence of injuries to the lower extremity. Many studies have investigated the relationship between dance injury and risk factors. However, risk factors for lower-extremity injury comparing recreational- and elite-level ballet dancers are scarce. Objective: To systematically review available original studies to assess risk factors for lower-extremity injury in female ballet dancers between recreational and elite ballet dancers. Data Sources: Five online databases [Web of Science, PubMed, OVID (Medline), EBSCO, and ProQuest] were searched systematically. Study Selection: Included studies had an analytic study design published in the past 11 years and investigated an association between potential risk factors and lower-extremity injury in female ballet dancers. Study Appraisal: Assessed independently by 2 reviewers using the Downs and Black (DB) criteria and Oxford Centre of Evidence-Based Medicine. Results: Seventeen studies were included. Alignment was a risk factor for lower-extremity injury in both recreational and elite ballet dancers. In elite ballet dancers, poor lumbopelvic movement control, inappropriate transversus abdominis contraction, decreased lower-extremity strength, and poor aerobic fitness were risk factors for lower-extremity injury. In recreational ballet dancers, hypermobility of the hip and ankle and longer training hours were risk factors for lower-extremity injury. Mean DB score was 15.94 (SD 1.57). The majority of studies were retrospective cohort studies or had poor follow-up, with 7 level 2b studies, 6 level 3b studies (cross-sectional), and 4 level 1b studies (prospective cohort with good follow-up). Conclusions: Alignment was identified as a common risk factor for recreational and elite ballet dancers. Other risk factors differed between recreational ballet dancers and elite ballet dancers. Future studies are warranted to use a prospective study design, identify dance level-specific risk factors, and implement evidence-based prevention strategies.